Studi Kasus: Terapi Mastitis Klinis pada Sapi Perah di Kota Batu - Hermawan, Intan Permatasari; Kurnianto, Ady; Kartikasari, Dian Ayu; Pratama, Junianto Wika Adi; Astuti, Mery (JURNAL KAJIAN VETERINER, 2024)
The purpose of this case report is to report a case of clinical mastitis in dairy cattle in Batu. One case was reported on this period. Anamnesis was carried out, the owner revealed that the cow did not produce milk and when milking the udderand nipples felt hard and the milk that wanted to come out seemed to be stuck. Physical examination was carried out, cow’s weight ±400 kg, body temperature 38.4 °C, the udder and nipple were swollen and inflamed, and decrease of milk production, mammae showed reddish and asymmetrical and painful when palpate. Based on the history and physical examination of the cow, it can be concluded that the cow was diagnosed with clinical mastitis with a fausta prognosis and the differential diagnosis was mammary tumour. The therapy given in this case was injection of the antibioticInterspectin-L® 10 ml, the anti-inflammatory and antipyretic Tolfedine® 10 ml intramuscularly.